Vanuatu : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Vanuatu. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that Vanuatu's economy is gradually recovering from the extensive damages caused by Cyclone Pam, which hit the country in March 2015. The cyclone led to a decline in GDP of about 0.8 percent in 2015. The current account deficit widened to 11 percent of GDP in 2015 from an average of 3 percent of GDP in the previous three years. Near-term prospects are favorable, but risks to the outlook are tilted to the downside. Real GDP growth is expected to reach 4 percent in 2016 and 4.5 percent in 2017 driven by the recovery in tourism and agriculture, and further ramping-up of infrastructure projects.